Ventilator Management in Acute Asthma - Jonathan Steinhofer; Roderick Morrison (Association of American Medical Colleges, 2011)
Abstract Introduction Asthma is an ever increasingly common diagnosis in the emergency room and clinics today. Knowing how to manage its acute presentation and complications is vital to becoming a competent physician in almost any specialty. Furthermore, the postintubation management of these patients is often overlooked despite its critical importance. Methods This simulation is a case-based experience designed to aid in teaching the initial management of an acute asthma exacerbation and ultimately the intricacies of ventilator management in such patients. It is displayed in outline form and meant to be enacted by medical professionals in-training, beginning with the initial presentation through intubation and disposition. The simulation should last approximately 15-30 minutes depending on the skill levels involved. Preparation should include a run through by the facilitator and actors prior to the actual simulation experience by learners. Ideally, the simulation requires a simulation room and mannequin, a facilitator to run the simulation, one actor playing the role of a nurse, and one actor acting as a parent. The simulation can be run with as little as two actors, a facilitator and imaginative learners. Results This case has been implemented within our curriculum as a residency simulation and has received excellent reviews from residents regarding its educational value. Discussion This case is designed to be run for a wide variety of medical professionals ranging from medical students to residents and faculty trained physicians. Although it is understood that there is a wide range of simulation environments, actual monitors, intubating equipment, and x-ray capabilities are ideal in order to make the experience as realistic as possible.